2005
DOI: 10.1248/bpb.28.747
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacokinetic Study of Intramuscular Administration of Bulleyaconitine A in Healthy Volunteers

Abstract: Bulleyaconitine A (BLA) (Fig. 1), a diester-diterpene type Aconitum alkaloid extracted from Aconitum longtounense T. L. MING, is a potent analgesic and anti-inflammatory agent, and can be used for the treatment of rheumatoid arthritis, osteoarthritis, periarthritis humeroscapularis, lumbar muscle strain, sprain, etc.1-3) The analgesic effect of BLA might be related to the 5-HT level in the brain, and no physical dependence has been observed. The relative analgesic effect of BLA was found to be as much as 3, 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…showed mean C max values of 2.11, 5.41, 11.47 and 19.97 ng/mL, respectively, and mean T 1/2 values of 2.48, 1.93, 2.17 and 1.23 h, respectively. Weng et al, [ 140 ] performed a pharmacokinetic study of bulleyaconitine A in humans. Ten healthy male volunteers were intramuscularly injected with 0.2 mg bulleyaconitine A and blood plasma samples were collected before and 0.17–15 h after injection.…”
Section: Clinical Applicability Of Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…showed mean C max values of 2.11, 5.41, 11.47 and 19.97 ng/mL, respectively, and mean T 1/2 values of 2.48, 1.93, 2.17 and 1.23 h, respectively. Weng et al, [ 140 ] performed a pharmacokinetic study of bulleyaconitine A in humans. Ten healthy male volunteers were intramuscularly injected with 0.2 mg bulleyaconitine A and blood plasma samples were collected before and 0.17–15 h after injection.…”
Section: Clinical Applicability Of Phytochemicalsmentioning
confidence: 99%
“…and soft gel capsule (p.o.) have been prescribed for the treatment of chronic pain and rheumatoid arthritis in China since 1980s [ 66 , 140 ]. Lappaconitine preparations have been also manufactured in China.…”
Section: Clinical Applicability Of Phytochemicalsmentioning
confidence: 99%
“…But they were tolerable and would disappear after some time. [4,5,22] It is possible that the biological activity of bulleyaconitine A may be caused by its toxicity rather than a specific pharmacological action. [23] However, King's group found that the anti-hypersensitivity of bulleyaconitine A can be separated from its neurotoxicity by the mechanism of action, [24] and the relatively wide therapeutic window of bulleyaconitine A suggests that its antinociception could be separated from its toxicity.…”
Section: Toxicities Of Bulleyaconitine Amentioning
confidence: 99%
“…[2][3][4] In 1980, bulleyaconitine A was firstly isolated from a folk herbal medicine Aconitum bulleyanum Diels, which was used for the treatment of chronic pain and rheumatoid arthritis in west Yunnan province by Kunming Institute of Botany, Chinese Academy of Science. [5] In 1980s, bulleyaconitine A has been approved by the China Food and Drug Administration as intramuscular injections, tablets and soft gel capsules for treating chronic pain, and rheumatoid arthritis in China.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since aconitum alkaloids are very unstable and decomposed fast in the human body, 3 metabolite studies are helpful to understand the medication safety, toxification and detoxification mechanism. Earlier publications have described methods for aconitine determination in biological samples, [4][5][6][7][8][9][10] and the identification of metabolites. [11][12][13] This paper reports on a pharmacokinetics study of aconitine metabolite in rat urine after oral administration for the first time, using a simple and selective liquid chromatography-tandem mass spectrometry (LC-MS/MS) method.…”
Section: Introductionmentioning
confidence: 99%